Histatin 5 inhibits adhesion of C. albicans to Reconstructed Human Oral Epithelium - Moffa, Eduardo B.; Mussi, Maria C. M.; Xiao, Yizhi; Garrido, Saulo S.; Machado, Maria A. A. M.; Giampaolo, Eunice T.; Siqueira, Walter L. (Frontiers in Microbiology, 2015)
Candida albicans is the most pathogenic fungal species, commonly colonizing on human mucosal surfaces. As a polymorphic species, C. albicans is capable of switching between yeast and hyphal forms, causing an array of mucosal and disseminated infections with high mortality. While the yeast form is most commonly associated with systemic disease, the hyphae are more adept at adhering to and penetrating host tissue and are therefore frequently observed in mucosal fungal infections, most commonly oral candidiasis. The formation of a saliva-derived protein pellicle on the mucosa surface can provide protection against C. albicans on oral epithelial cells, and narrow information is available on the mucosal pellicle composition. Histatins are one of the most abundant salivary proteins and presents antifungal and antibacterial activities against many species of the oral microbiota, however, its presence has never been studied in oral mucosa pellicle. The objective of this study was to evaluate the potential of histatin 5 to protect the Human Oral Epithelium against C. albicans adhesion. Human Oral Epithelial Tissues (HOET) were incubated with PBS containing histatin 5 for 2 h, followed by incubation with C. albicans for 1 h at 37°C. The tissues were then washed several times in PBS, transferred to fresh RPMI and incubated for 16 h at 37°C at 5% CO2. HOET were then prepared for histopathological analysis using light microscopy. In addition, the TUNEL assay was employed to evaluate the apoptosis of epithelial cells using fluorescent microscopy. HOET pre-incubated with histatin 5 showed a lower rate of C. albicans growth and cell apoptosis when compared to the control groups (HOET alone and HOET incubated with C. albicans). The data suggest that the coating with histatin 5 is able to reduce C. albicans colonization on epithelial cell surfaces and also protect the basal cell layers from undergoing apoptosis.